Korean Wave Creating New Appetite Beyond Entertainment: The Role of the Korean Entertainment Industry in Promoting Korean Culture - Wijesinghe, Hashan; Karunasena, Vithakshi; Suduwelikanda, Daupadi; Iddagoda, Sanduni (Technium Social Sciences Journal, 2025)
The growing influence of the Korean entertainment industry is well documented. Since the late 1990s, the Korean wave or Hallyu has continued to have an unprecedented influence on the lives of people across the world. Until recent times, gastrodiplomacy remained a government-to-people affair where the Government of a particular country organises various programs to promote its cuisine abroad. Against this backdrop, this research investigates the role of K-dramas in promoting Korean cuisine among the international viewership. This study looks at the impact the K-dramas have had on the food preferences of Sri Lankan viewers and uses a mixed research design, and both primary and secondary data are used to address the research objectives. A total of 145 e-questionnaires were distributed. These questionnaires were predominantly closed-ended and analysed using frequency analysis. Apart from the questionnaires, a total of 20 in-depth interviews were conducted to better understand the impact of K-dramas on the food preferences of Sri Lankan viewership. These open-ended questions were analysed using descriptive method. As per the findings, K-dramas have a significant impact on the food preferences of the Sri Lankan viewership, where 93.8% admitted that K-dramas made them try out Korean cuisine. In conclusion, while this study contributes to the literature on the growing influence of the Korean entertainment industry on the lives of people, it also underscores the impact the Korean entertainment industry has on promoting various cultural products among the international community.